Methodological approach to the determination of the place of municipal education in the economic space of the region - V. I. Kondratyeva; V. L. Pulyaevskaya; В. И. Кондратьева; В. Л. Пуляевская (Novosibirsk State University of Economics and Management, 2018)
Huge territory of the Republic of Sakha (Yakutia) and underdevelopment of transport and energy infrastructure predetermine the need for development of new approaches and algorithms of complex dimensional analysis of the level of social and economic condition of municipal formations. The article considers description of the system of indicators of data, which form the basis of the database and reflect spatial social and economic processes at the level of population clusters, municipal regions and economic zones of the Republic of Sakha (Yakutia). At the moment there are a lot of approaches to assessment of the level of development of territories. The whole variety of the methods, used for assessment of the level of development of municipal formations, comes down to two categories. The first group is based on determination of particular indicators and calculation of the generalizing index on their basis. The second group of methods includes econometric assessments, where efforts to reveal cause-effect relations of municipal development are carried out. Distribution of municipal formations by groups is presented in the basis of per capita municipal product indicator; the distribution makes it possible to assess the level of social and economic development and significance of each municipal formation for economy of the region. The contribution of Lensky district to formation of GRP of the republic is analyzed; the district holds leading positions in macroeconomic indicators and makes a significant contribution to social and economic development of the republic. Forecasts of spatial development of the region require consideration of the approaches to development of the economic and mathematical model of dynamic interrelation between factors of economic advancement with allowance for individual characteristics of the territories. The article presents a long-time forecast of GWP indicator for two scenarios of development of Lensky district as an example. Имея значительную территорию Республики Саха (Якутия), ...